Coaches’ Subjective Perceptions and Physical Performance: Key Factors in Youth Football Talent Identification—An Exploratory Study - Federico Abate Daga; Ruben Allois; Massimiliano Abate Daga; Franco Veglio; Samuel Agostino (Education Sciences)
This study examines the subjective attributes that coaches consider most important for identifying and developing the talent of junior élite football players. It also explores whether players’ physical fitness efficiency moderates these attributes and influences playing time during the regular season. Forty-three junior élite football players and four Italian Serie A club coaches participated in the study, contributing their unique perspectives and experiences. Players’ physical fitness was assessed using the Yo-Yo Intermittent Recovery Level 1 test, while coaches rated players’ abilities through a structured questionnaire. A significant positive relationship was found between ’understanding of the game and position on the field’ and total playing time (t = 3.498, p < 0.01, β = 0.953). Physical efficiency further strengthened this relationship when players’ fitness levels were average (b = 0.624, p < 0.001) and one standard deviation above the mean (b = 0.891, p < 0.001). These findings highlight the importance of tactical awareness in earning playing time and suggest that physical fitness enhances the effect of cognitive abilities on performance. This study provides insights into how coaches assess talent and underscores the value of integrating physical and tactical development in youth football, providing a testament to the power of collaboration in advancing our understanding of talent identification in sports.